Metahuman Studies, Choral Ontopolitics and Earth Liberation - Val, Jaime del (Journal of Posthumanism, 2023)
Metahumanism is presented as an evolution from critical posthumanism both in terms of an intensified critique of the Planetary Holocaust and of a radical pragmatics of becoming based on a movement philosophy which has diverse precursors back to the pre-Socratics and beyond. Metahuman studies and its critical counterpart in Trash-human studies is the corresponding studies field promoted by the Metahuman Futures Forum, an alternative whose urgency is justified due to the prevailing human supremacism in other existing intellectual and activist milieus, and which culminates in the performative proposal for a ‘Trial against Humanity’. A choral politics of moving bodies is introduced through the Vision Statement of the Bodynet-Khorós EU project, aiming at a liberation of al life forms from human dominion and its extinction loop, for a metahuman r/evolution.